The Impact of Augmented Reality on the Social Skills of Children with High Functioning Autism - Morteza Bakhtiarvand (Randwick International of Social Science Journal, 2021)
The present study determined the effectiveness of augmented reality on the social skills of children with high Functioning autism. The present study was a quasi-experimental study with a posttest test with a control group. The statistical population of the present study included all children with autism with high performance in Andimeshk in 2019. Participants included 20 children with high-functioning autism who were selected by available sampling method and randomly selected in the experimental and control groups. They were evaluated using the Bellini social profile, and then augmented reality was performed on the experimental group in 10 45-minute sessions, while not on the control group. The findings were analyzed using covariance analysis and showed that the augmented reality intervention program had an effect on the social skills of children with high-functioning autism. Based on these results, augmented reality intervention program can be considered as a priority for rehabilitation of children with autism with high performance.